Dynamics of scalp potential and autonomic nerve activity during intelligence test - Amin, H.U. (2013)
The main objective of this study was to examine the changes in autonomic nervous system (ANS) and scalp potential during intelligence test (IQ). Electroencephalogram (EEG) and Electrocardiogram (ECG) signals were recorded simultaneously from eight healthy participants during IQ and resting states (eyes-closed and eyes-open). Heart rate (HR) and heart rate variability (HRV) were derived from ECG signal. EEG mean power was computed for five frequency bands (delta, theta, alpha, beta, and gamma) and analyzed in 12 regions across the scalp. The EEG frequency bands showed significant (p<0.025) changes between IQ test and rest states. Delta and theta at frontal (PF, AF, F) and temporal regions (FT, T, TP) and alpha activity at parietal (P), parietooccipital (PO) and occipital (O) regions were significant. In beta and gamma bands, highly reduced mean power was found at P, PO, and O regions as compared to PF, AF, and F regions in IQ test. HR and low frequency in normalized unit (LFnu) were increased significantly (p<0.05 and p<0.025, respectively) in IQ test. Further, high frequency in normalized unit (HFnu) was decreased (p<0.11). Results showed parallel changes in scalp potential and automatic nervous activity during IQ test compared to rest conditions. Â© Springer-Verlag 2013.